2016
DOI: 10.1021/acssynbio.6b00143
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the High-Value Plant Secondary Product Benzyl Isothiocyanate via Functional Expression of Multiple Heterologous Enzymes in Escherichia coli

Abstract: Plants produce a wide variety of secondary metabolites that are highly nutraceutically and pharmaceutically important. Isothiocyanates, which are found abundantly in cruciferous vegetables, are believed to reduce the risk of several types of cancers and cardiovascular diseases. The challenges arising from the structural diversity and complex chemistry of these compounds have spurred great interest in producing them in large amounts in microbes. In this study, we aimed to synthesize benzyl isothiocyanate in Esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Specifically, it has been reported that the consumption of cruciferous vegetables is associated with reduced risk of cancer development, a capacity associated with their high content of sulfur-containing phytochemicals known as isothiocyanates (ITCs) [23][24][25][26]. These are secondary metabolites obtained from hydrolysis of their precursor molecules (glucosinolates), by myrosinase, an enzyme activated after plant tissue disruption [27] (Figure 1). The importance of ITCs as nutraceutical agents is reflected upon their capacity to modulate enzymes involved in (i) detoxification, (ii) apoptotic induction, (iii) cell cycle growth arrest and (iv) interactions with various other cellular pathways of tumor growth and invasion known to be deregulated in various cancers including MM [28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has been reported that the consumption of cruciferous vegetables is associated with reduced risk of cancer development, a capacity associated with their high content of sulfur-containing phytochemicals known as isothiocyanates (ITCs) [23][24][25][26]. These are secondary metabolites obtained from hydrolysis of their precursor molecules (glucosinolates), by myrosinase, an enzyme activated after plant tissue disruption [27] (Figure 1). The importance of ITCs as nutraceutical agents is reflected upon their capacity to modulate enzymes involved in (i) detoxification, (ii) apoptotic induction, (iii) cell cycle growth arrest and (iv) interactions with various other cellular pathways of tumor growth and invasion known to be deregulated in various cancers including MM [28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Given that many of the identified metabolizers of the GSLs include groups of beneficial bacteria such as the lactobacilli and bifidobacteria that are often utilized as probiotics, this opens up potential opportunities to exploit such bacteria as dietary supplements with GSL‐containing foods that would provide health benefits particularly to low ITC secreting individuals as part of their personalized nutrition. Recently, a study has looked at the potential for expressing the glucotropaeolin biosynthetic pathway in E. coli together with a myrosinase of B. brassicae with some success as the authors were able to show the in vitro formation of benzylisothiocyanate . If this technology can be developed where ITCs are actually produced during fermentation then it could potentially allow the delivery of sulforaphane in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the desulphoglucosinolate: PAPS-SULT from Arabidopsis thaliana (Col-0 ecotype) and the myrosinase from Brevicorynebrassicae (aphid) were used. The biosynthesis of benzyl isothiocyanates by the combined expression of in vitro optimized enzymes was confirmed by GC-MS analysis (Liu et al, 2016).…”
Section: Saccharothrixespanaensismentioning
confidence: 83%